(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Metric spaces, which generalize the properties of usually experienced physical and abstract spaces into a mathematical structure. This paper will acquaint the peruser with the idea of metric spaces and continuity. A ton accentuation has been given to propel the thoughts under talk to enable the peruser to create ability in utilizing his creative mind to envision the abstract idea of the subject. Assortment of examples alongside genuine applications have been given to comprehend and value the excellence of metric spaces.